2002
DOI: 10.1101/gad.953802
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ knockdown by engineered transcription factors: exogenous PPARγ2 but not PPARγ1 reactivates adipogenesis

Abstract: To determine functional differences between the two splice variants of PPAR␥ (␥1 and ␥2), we sought to selectively repress ␥2 expression by targeting engineered zinc finger repressor proteins (ZFPs) to the ␥2-specific promoter, P2. In 3T3-L1 cells, expression of ZFP55 resulted in >50% reduction in ␥2 expression but had no effect on ␥1, whereas adipogenesis was similarly reduced by 50%. However, ZFP54 virtually abolished both ␥2 and ␥1 expression, and completely blocked adipogenesis. Overexpression of exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
212
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(226 citation statements)
references
References 31 publications
5
212
0
5
Order By: Relevance
“…15 Most TF ZF s have been constructed for constitutive regulation of natural promoters driving reporter genes. 11,16,17 TF ZF s have been expressed from constitutive promoters transiently, retrovirally or by generating integrated stable cell lines [18][19][20][21] and have also been expressed in vivo. 22 To effectively study gene function and develop gene therapies, tightly controlled and highly inducible regulation of the target gene is desirable through direct control of the TF ZF with a cell-penetrating drug.…”
Section: Introductionmentioning
confidence: 99%
“…15 Most TF ZF s have been constructed for constitutive regulation of natural promoters driving reporter genes. 11,16,17 TF ZF s have been expressed from constitutive promoters transiently, retrovirally or by generating integrated stable cell lines [18][19][20][21] and have also been expressed in vivo. 22 To effectively study gene function and develop gene therapies, tightly controlled and highly inducible regulation of the target gene is desirable through direct control of the TF ZF with a cell-penetrating drug.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address the contribution of different PPAR isoforms in adipocyte differentiation, Ren and co-workers silenced expression of PPAR 1 and PPAR 2 in 3T3-L1 cells using zinc finger repressor proteins [30]. By employing this approach it was demonstrated that ectopic expression of PPAR 2 but not PPAR 1 is able to restore adipogenesis.…”
Section: Page 7 Of 25mentioning
confidence: 99%
“…ZFP-TFs have been tested in many settings [9][10][11][12][13], and recent work, for example, has shown how they can induce vascular endothelial growth factor A expression and thus stimulate the growth of new blood vessels in mice [14].…”
Section: ® Rapid Communicationmentioning
confidence: 99%